Assessing the feasibility of a neck‐strength training intervention in university women's rugby - Freja Petrie (European Journal of Sport Science, 2024)
Cervical muscle strength has been demonstrated to reduce concussion risk in high school athletes, and interventions to improve this in male rugby players have elicited strength improvements. However, the feasibility of introducing neck-strengthening interventions in women’s rugby has not been investigated. This study sought to pilot a neck-strength intervention in a population of university-level women’s rugby players.A fixed-frame dynamometer was used to assess the multi-directional isometric neck-strength of fourteen university women’s rugby players (20.3 ± 1.0 years). Between baseline and end-of-season testing, a neck-strengthening program was completed. Interviews were conducted with six players and two coaches to understand program engagement. Interviews were transcribed verbatim and processed via inductive content analysis. Increases in absolute neck-strength post-intervention in left and right lateral flexion (left 85.4 ± 29.7 N to 108.2 ± 41.6 N, p=0.02, right 87.4 ± 33.3 N to 40.3 N, p=0.01) and flexion (128.4 ± 28.8 N to 147.9 ± 30.5 N, p=0.01) were perceived positively by the players although there were suggestions that greater adaptability according to training age and more variety was required. Participants initially demonstrated limited awareness of neck-strength training but engaged well with the exercises once the potential benefits were understood.This intervention shows promise as an effective, palatable strategy to improve neck-strength in university women’s rugby players. Further research is needed to establish whether such improvements in neck-strength are associated with meaningful reductions in head impact occurrence.